Valorization of Brewery Waste through Polyhydroxyalkanoates Production Supported by a Metabolic Specialized Microbiome - Carvalheira, Mónica (2022)
project LA/P/0140/2020 of the Associate Laboratory Institute for Health and Bioeconomy—i4HB. Publisher Copyright: © 2022 by the authors.